Resting-state Functional Magnetic Resonance Imaging Identifies Cerebrovascular Reactivity Impairment in Patients With Arterial Occlusive Diseases: A Pilot Study. Issue 5 (20th September 2018) - Nishida, Sei; Aso, Toshihiko; Takaya, Shigetoshi; Takahashi, Yuki; Kikuchi, Takayuki; Funaki, Takeshi; Yoshida, Kazumichi; Okada, Tomohisa; Kunieda, Takeharu; Togashi, Kaori; Fukuyama, Hidenao; Miyamoto, Susumu
Abstract: BACKGROUND: The development of noninvasive approaches for identifying hypoperfused brain tissue at risk is of major interest. Recently, the temporal-shift (TS) maps estimated from resting-state blood oxygenation level-dependent (BOLD) signals have been proposed for determining hemodynamic state. OBJECTIVE: To examine the equivalency of the TS map and the cerebrovascular reactivity (CVR) map derived from acetazolamide-challenged single-photon emission computed tomography (SPECT) in identifying hemodynamic impairment in patients with arterial occlusive diseases. METHODS: Twenty-three patients with arterial occlusive diseases who underwent SPECT were studied. With a recursive TS analysis of low-frequency fluctuation of the BOLD signal, a TS map relative to the global signal was created for each patient. The voxel-by-voxel correlation coefficient was calculated to examine the image similarity between TS and SPECT-based cerebral blood flow (CBF) or CVR maps in each patient. Furthermore, simple linear regression analyses were performed to examine the quantitative relationship between the TS of BOLD signals and CVR in each cerebrovascular territory. RESULTS: The within-patient, voxel-by-voxel comparison revealed that the TS map was more closely correlated with SPECT-CVR map ([Z( r )] = 0.42 ± 0.18) than SPECT-CBF map ([Z( r )] = 0.058 ± 0.11; P  < .001, paired t -test). The regression analysis showed a significant linear association between the TS of BOLD signals and CVR in the anterior circulation where the reduction of CVR was evident in the patient group. CONCLUSION: BOLD TS analysis has potential as a noninvasive alternative to current methods based on CVR for identification of tissue at risk of ischemic stroke.